Model Online Shopping Intensity pada Mahasiswa Perantau: Peran Loneliness, Social Media Addiction, dan Emotional Buying - Masyitah Febranti Hamzah; Ramli S; Rezki Wardani (Journal of Management Branding, 2026)
This study aims to examine the effect of loneliness and social media addiction on online shopping intensity through emotional buying as a mediating variable among migrant students in West Sulawesi Province. The novelty of this research lies in the proof of the integrative S-O-R model that positions emotional buying as the sole mediator linking psychological conditions to online shopping intensity. This study used a quantitative approach with a cross-sectional design, involving 276 migrant student respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) based on AMOS Version 31. The results showed that loneliness and social media addiction had no significant direct effect on online shopping intensity, but both had a positive and significant effect on emotional buying. Emotional buying was proven to act as a full mediator linking psychological factors to online shopping intensity. These findings conclude that the psychological condition of migrant students does not directly determine online shopping intensity, but must first go through an affective process in the form of emotional buying.